Prevalence of Antimicrobial Resistance in Escherichia coli Isolated From Guinea Pigs in Andean Peru. - Gamarra-Ramírez, R. (2025)
Background: Guinea pig breeding has gained increasing economic and nutritional importance in various regions worldwide. However, guinea pig farming exposes livestock to multiple infectious diseases that require treatment with different antibiotics—leading to resistance if not properly managed. Objectives: This study aimed to determine the prevalence of bacterial resistance in Escherichia coli isolated from guinea pigs raised in Cajamarca City, Peru, against five commonly used antimicrobials in 2022. Methods: Rectal swabs were collected from 105 clinically healthy guinea pigs with no history of antibiotic treatment. The identification of E. coli was confirmed through IMViC biochemical tests, and antimicrobial susceptibility was assessed using the disk diffusion method. Results: All samples showed resistance to at least one antibacterial. According to the The European Food Safety Authority (EFSA)-European Centre for Disease Prevention and Control (ECDC) classification, the prevalence of neomycin resistance was “extremely high (>70%),” of sulfamethoxazole/trimethoprim and chloramphenicol “low (>1-10%)” and of tetracycline and enrofloxacin “very low (>0.1-1%).” Additionally, 93 cultures (88.57%) were resistant to only one antibacterial, eight (7.62%) to two antibacterials, and only two (1.90%) to three antibacterials. Conclusion: A high prevalence of neomycin resistance was observed in E. coli isolated from guinea pigs. Antibacterials with low resistance prevalences are an alternative for use in these rodents. However, continuous monitoring of antimicrobial susceptibility profiles and specific implementation and sustainable strategies are necessary to preserve the efficacy of antibacterials with high sensitivity rates.